Posthumous Performance and Digital Resurrection: From Science Fiction to Startups - Leaver, Tama (Routledge, 2019)
This chapter examines the promotional discourse deployed by three of the futuristic start-up companies-LivesOn, Eterni.me and Humai. It compares with several notable science fiction (SF) texts in two levels which explore the underlying presumptions and broader cultural and social ramifications of these companies succeeding in achieving digital resurrection. First, to ask what presumptions are being made about contemporary personhood, culture and death. Second, mapping what future issues the success of these start-ups might actually provoke. Notably, the Black Mirror series revisited the theme of digital life after death in the third season, the first on the streaming service Netflix. Many of the SF stories which have followed in Frankenstein's wake explore the complex social, ethical and political questions of technology being a conduit to a form of reincarnation. These stories are especially important today as digital resurrection becomes a sales pitch for new tech start-ups.